Professor Kessler: scientist, educator, organizer and popularizer of science - Gamaliia, V. M. (History of science and technology, 2013)
The article is dedicated to the activities of prominent zoologist of nineteenth century K. Kessler. Particular attention is paid to his work at Zoology Department of Kiev’s St. Vladimir University and the contribution of a researcher into the organization of congresses and the Society of Naturalists. The role of K. Kessler in the popularization of Darwin’s theory of evolution is shown too.